Research progress on the mechanisms of polysaccharides derived from traditional Chinese medicine in the treatment of Parkinson’s disease - Zhou, Xiangling; Pan, Qi (Frontiers in Pharmacology, 2025)
Parkinson’s disease (PD) is currently a highly prevalent neurodegenerative disease. Its pathogenesis is complex, and there is no effective method to prevent the disease progression. Traditional Chinese medicine (TCM) has a unique advantage in treating PD through the approach of syndrome differentiation. TCM prescriptions for PD can reduce Unified Parkinson’s Disease Rating Scale (UPDRS) scores, improve non-motor symptoms, and decrease adverse drug reactions. Bioactive polysaccharides extracted from prescribed Chinese herbs exhibit diverse biological activities due to their wide range of botanical sources. This review summarizes the pharmacological mechanisms of polysaccharides derived from TCM in managing PD, including inhibition of apoptosis, activation of autophagy, regulation of inflammation, anti-oxidative stress, improvement of mitochondrial function, and neuroprotective effects, aiming to provide a theoretical basis for future research and treatment.